Incorporating automatic speech recognition methods into the transcription of police-suspect interviews: factors affecting automatic performance - Harrington, Lauren (Frontiers in Communication, 2023)
In England and Wales, transcripts of police-suspect interviews are often admitted as evidence in courts of law. Orthographic transcription is a time-consuming process and is usually carried out by untrained transcribers, resulting in records that contain summaries of large sections of the interview and paraphrased speech. The omission or inaccurate representation of important speech content could have serious consequences in a court of law. It is therefore clear that investigation into better solutions for police-interview transcription is required. This paper explores the possibility of incorporating automatic speech recognition (ASR) methods into the transcription process, with the goal of producing verbatim transcripts without sacrificing police time and money. We consider the potential viability of automatic transcripts as a 'first' draft that would be manually corrected by police transcribers. The study additionally investigates the effects of audio quality, regional accent, and the ASR system used, as well as the types and magnitude of errors produced and their implications in the context of police-suspect interview transcripts. Speech data was extracted from two forensically-relevant corpora, with speakers of two accents of British English: Standard Southern British English and West Yorkshire English (a non-standard regional variety). Both a high quality and degraded version of each file was transcribed using three commercially available ASR systems: Amazon, Google and Rev. System performance varied depending on the ASR system and the audio quality, and while regional accent was not found to significantly predict word error rate, the distribution of errors varied substantially across the accents, with more potentially damaging errors produced for speakers of West Yorkshire English. The low word error rates and easily identifiable errors produced by Amazon suggest that the incorporation of ASR into the transcription of policesuspect interviews could be viable, though more work is required to investigate the effects of other contextual factors, such as multiple speakers and different types of background noise.